CIRCULAR RESECTION OF THE CENTRAL PART OF THE LARGE DIAGNOSE WITH ONCOLOGICAL STENOSIS (clinical case) - S. Ismailov; T. Akpanbetov; B. Abetayev; M. Zhanteyev; A. Aripbek (Yassawi Journal of Health Sciences, 2026)
Because laryngeal stenosis leads to progressive respiratory failure, most patients with this condition require surgical treatment. Tracheal stenosis can be caused by injuries, infectious diseases, cicatricial strictures developing after tracheostomy or intubation, as well as tracheal tumors. The issue calls for improving surgical treatment methods for tracheal stenosis and refining anesthesiological intervention techniques. To improve the level of surgical treatment for tracheal stenosis by taking into account the tumor's location, growth direction, length of the narrowing, the risks and benefits of surgical therapy, and the specifics of anesthesiological interventions. A patient with subglottic carcinoma developed a tracheal stenosis. Airflow through the trachea became severely obstructed, forcing them to breathe on humidified oxygen for several weeks. Due to respiratory failure, he was referred to an oncology clinic and underwent surgical treatment. Tracheoscopy revealed an exophytic tumor measuring 2x3 cm, extending from the mucosa of the lower larynx to the level of the second tracheal ring and occupying more than 80% of the tracheal lumen. The operation began with intubation under general anesthesia through a tracheostomy tube. After the skin was prepared and the tumor area was completely excised, hemostasis was achieved, and then a circular incision was made below the tumor, including two tracheal rings. Hyperoxemia was achieved before the tracheal incision, and temporary artificial apnea was established during the cut. After the tracheal incision, the endotracheal tube was repositioned below the incision site, and anesthesia was continued. After the tumorous portion of the trachea was completely excised, the endotracheal tube was repositioned. Running sutures were placed between the tracheal rings along the tube, tightened, and secured to create a watertight seal. After an aseptic dressing was applied to the wound, the thyroid cartilage was sutured to the chest skin to prevent tracheal elongation. There are no signs of respiratory insufficiency The course and outcomes of tracheal circular resection surgery were discussed at the Oncology Center Clinical Conference, highlighting its challenges and successes, as well as the specifics of anesthesia. Improving the surgical treatment options and anesthesia management for tracheal stenosis caused by cancer or other factors.